Life cycle evolution and systematics of Campanulariid hydrozoans - Govindarajan, Annette Frese, 1970- (Massachusetts Institute of Technology, 2004)
Thesis (Ph. D.)--Joint Program in Oceanography/Applied Ocean Science and Engineering (Massachusetts Institute of Technology, Dept. of Biology; and, the Woods Hole Oceanographic Institution), 2004. Includes bibliographical references. The purpose of this thesis is to study campanulariid life cycle evolution and systematics. The Campanulariidae is a hydrozoan family with many life cycle variations, and provide an excellent model system to study life cycle evolution. Additionally, the unique campanulariid Obelia medusae may have been "re-invented" from ancestors without medusae. Chapter 1 reviews campanulariid life cycles and taxonomy. Chapter 2 presents a phylogeny based on 18S rDNA, calmodulin, 16S rDNA and cytochrome c oxidase I (COI). Ancestral life cycles are reconstructed using parsimony. Medusa loss is common, and Obelia may derive from ancestors with typical medusae. Taxonomic results are discussed in Chapter 3. Billardia, a nominal campanulariid, appears phylogenetically distant, while Bonneviella spp. (Bonneviellidae), are nested within the Campanulariidae. Campanulariid genera are not monophyletic. Orthopyxis integra and Clytia gracilis may represent cryptic species, while Obelia longissima may be cosmopolitan. Chapter 4 investigates Obelia geniculata phylogeography. Japanese and North Atlantic 16S rDNA and COI sequences are calibrated against the opening of the Bering Strait. Substitution rates are faster than in anthozoans and comparable to non-cnidarian invertebrates. Comparison of Pacific and Atlantic sequences suggests cryptic species exist. Finally, hydroids in New Brunswick, Canada and Iceland may have survived the last glaciation. by Annette Frese Govindarajan. Ph.D.